Paternal advanced age and sperm quality are indicators for Preimplantation Genetic Testing in egg donation cycles - Jeimy Pedraza; Hugo Sierra; Jacqueline Cordero; Esther López-Bayghen (IMR Press, 2021)
Background: A wide variety of studies demonstrate the influence of the oocyte source's age on the success of assisted reproduction treatments; however, the effect of paternal age has been studied to a lesser extent. Therefore, our goal was to assess the impact of male age and sperm quality on in vitro fertilization (IVF) outcomes. Methods: Three hundred ninety-four ova donation IVF cycles from Ingenes México were retrospectively analyzed. All ova donors (age range: 18-35 years) underwent a similar IVF stimulation protocol. The oocytes were aspirated and inseminated by intracytoplasmic sperm injection (ICSI) using either partner sperm (n = 332, age: 42.4 ± 7.4 years) or donor sperm (n = 62, age: 25.0 ± 3.3 years). Semen characteristics were evaluated by a seminogram. Biopsies were performed on Day 5 or Day 6, and Preimplantation Genetic Testing for Aneuploidies (PGT-A) was used to determine chromosome integrity with Next-Generation Sequencing. Results: A total of 1449 embryos were biopsied, 995 Day 5 and 454 Day 6. The aneuploidy rates for Day 5 and Day 6 embryos were not significantly different (22.2% and 22.7%, respectively). Independent of the sperm source, there was no observable trend between embryo aneuploidy rates and the sperm source's age; however, when considering paternal sperm with teratozoospermia, a significant association was observed (rho = 0.165, p = 0.041). Sperm quality showed no effect on fertilization rates, blastocyst formation, or implantation rates. Discussion: Here, the sperm source's age did not affect the aneuploidy rate nor embryo implantation; however, with teratozoospermia, there was a weak association between the aneuploidy rate and age. Therefore, it would be prudent to perform PGT-A when advanced age and teratozoospermia are detected.